Social isolation and its relationship to multidimensional poverty - Samuel, K; Alkire, S; Hammock, J; Mills, C; Zavaleta, D (2014)
Most governments and policy makers define poverty by income. Yet poor people define their poverty more broadly, including lack of education, health, housing, empowerment, employment, personal security and more. As such, no one factor is able to capture all the aspects that contribute to poverty, making poverty a multidimensional concept. One dimension of poverty that has been often overlooked is social connectedness. This paper argues that social connectedness is an important missing ingredient of multidimensional poverty, with social isolation being a central component. We illustrate the concepts of social isolation and social connectedness using examples from South Africa and Mozambique, and the First Nations of Canada, as well as the work of Special Olympics International around the world.